SOME ASPECTS REGARDING REGIONALIZATION IN THE EUROPEAN UNION - Ion, POPESCU; Cosmin-Ionut, ENESCU (Strategii Manageriale, 2014)
Regional development policies initiated in the last decades, European countries, aimed at recovery economic and social development locally, economic recovery less developed areas, reducing disparities between the levels of development of the regions. In the EU, there is no compulsory law or practice concerning regionalization. This means that there is no unique model which ought to be implemented without discussion by all the candidates / members. Indeed the EU indicates no model at all, it rather prefers to leave the States free to decide on their own an institutional architecture, based on their own historical path. By doing so, the EU intends to avoid the troubles linked to the variety of social situations inherited from the long term history. It hopes, moreover, that provided the formal aspects are respected, the citizen will be able to take possession of their own institutions and will play the game of multi level governance.